Clinical Confirmation of Pan-Amyloid Reactivity of Radioiodinated Peptide 124I-p5+14 (AT-01) in Patients with Diverse Types of Systemic Amyloidosis Demonstrated by PET/CT Imaging - Emily B. Martin; Alan Stuckey; Dustin Powell; Ronald Lands; Bryan Whittle; Craig Wooliver; Sallie Macy; James S. Foster; Spencer Guthrie; Stephen J. Kennel; Jonathan S. Wall (MDPI AG, 2023)
There are at least 20 distinct types of systemic amyloidosis, all of which result in the organ-compromising accumulation of extracellular amyloid deposits. Amyloidosis is challenging to diagnose due to the heterogeneity of the clinical presentation, yet early detection is critical for favorable patient outcomes. The ability to non-invasively and quantitatively detect amyloid throughout the body, even in at-risk populations, before clinical manifestation would be invaluable. To this end, a pan-amyloid-reactive peptide, p5+14, has been developed that is capable of binding all types of amyloid. Herein, we demonstrate the ex vivo pan-amyloid reactivity of p5+14 by using peptide histochemistry on animal and human tissue sections containing various types of amyloid. Furthermore, we present clinical evidence of pan-amyloid binding using iodine-124-labeled p5+14 in a cohort of patients with eight (n = 8) different types of systemic amyloidosis. These patients underwent PET/CT imaging as part of the first-in-human Phase 1/2 clinical trial evaluating this radiotracer (NCT03678259). The uptake of 124I-p5+14 was observed in abdominothoracic organs in patients with all types of amyloidosis evaluated and was consistent with the disease distribution described in the medical record and literature reports. On the other hand, the distribution in healthy subjects was consistent with radiotracer catabolism and clearance. The early and accurate diagnosis of amyloidosis remains challenging. These data support the utility of 124I-p5+14 for the diagnosis of varied types of systemic amyloidosis by PET/CT imaging.